Managing a Circular Food System in Sustainable Urban Farming. Experimental Research at the Turku University Campus (Finland) - Erälinna Leena; Szymoniuk Barbara (MDPI, 2022)
People around the world pay increasingly more attention to health, social, environmental, and ethical issues. As a consequence, they seek value in food that is fresh, less processed, and sustainably sourced. The article presents an experimental project supporting the implementation of a circular food system in the city of Turku, Finland. The outcome of the project is a globally replicable concept of managing a local circular food system in sustainable urban farming. The project had two objectives: (1) to reduce food waste in restaurants in the Turku University Campus; (2) to support local recycling of nutrients by composting food waste generated in the pilot restaurant and reuse the nutrients in the process of urban farming. The presented concept is based on the results of two experimental studies. It ties in with UN and EU sustainable development strategies and policies, e.g., Sustainable Development Goals (2, 11, and 12), the European Green Deal, the Farm to Fork Strategy, and the concepts of Circular Economy and Sustainable Cities.